The Long-Term Immunity of a Microneedle Array Patch of a SARS-CoV-2 S1 Protein Subunit Vaccine Irradiated by Gamma Rays in Mice - Eun Kim; Muhammad S. Khan; Juyeop Shin; Shaohua Huang; Alessandro Ferrari; Donghoon Han; Eunjin An; Thomas W. Kenniston; Irene Cassaniti; Fausto Baldanti; Dohyeon Jeong; Andrea Gambotto (Vaccines)
Background/Objectives: COVID-19 vaccines effectively prevent severe disease, but unequal distribution, especially in low- and middle-income countries, has led to vaccine-resistant strains. This highlights the urgent need for alternative vaccine platforms that are safe, thermostable, and easy to distribute. This study evaluates the immunogenicity, stability, and scalability of a dissolved microneedle array patch (MAP) delivering the rS1RS09 subunit vaccine, comprising the SARS-CoV-2 S1 monomer and RS09, a TLR-4 agonist peptide. Methods: The rS1RS09 vaccine was administered via MAP or intramuscular injection in murine models. The immune responses of the MAP with and without gamma irradiation as terminal sterilization were assessed at doses of 5, 15, and 45 µg, alongside neutralizing antibody responses to Wuhan, Delta, and Omicron variants. The long-term storage stability was also evaluated through protein degradation analyses at varying temperatures. Results: The rS1RS09 vaccine elicited stronger immune responses and ACE2-binding inhibition than S1 monomer alone or trimer. The MAP delivery induced sgnificantly higher and longer-lasting S1-specific IgG responses for up to 70 weeks compared to intramuscular injections. Robust Th2-prevalent immune responses were generated in all the groups vaccinated via the MAP and significant neutralizing antibodies were elicited at 15 and 45 µg, showing dose-sparing potential. The rS1RS09 in MAP has remained stable with minimal protein degradation for 19 months at room temperature or under refrigeration, regardless of gamma-irradiation. After an additional month of storage at 42 °C, cit showed less than 3% degradation, ompared to over 23% in liquid vaccines Conclusions: Gamma-irradiated MAP-rS1RS09 is a promising platform for stable, scalable vaccine production and distribution, eliminating cold chain logistics. These findings support its potential for mass vaccination efforts, particularly in resource-limited settings.